2004
DOI: 10.1128/mcb.24.19.8691-8704.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Hinge-Helix 1 Region of Peroxisome Proliferator-Activated Receptor γ1 (PPARγ1) Mediates Interaction with Extracellular Signal-Regulated Kinase 5 and PPARγ1 Transcriptional Activation: Involvement in Flow-Induced PPARγ Activation in Endothelial Cells

Abstract: Peroxisome proliferator-activated receptors (PPAR) are ligand-activated transcription factors that form a subfamily of the nuclear receptor gene family. Since both flow and PPAR␥ have atheroprotective effects and extracellular signal-regulated kinase 5 (ERK5) kinase activity is significantly increased by flow, we investigated whether ERK5 kinase regulates PPAR␥ activity. We found that activation of ERK5 induced PPAR␥1 activation in endothelial cells (ECs). However, we could not detect PPAR␥ phosphorylation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(165 citation statements)
references
References 43 publications
6
156
3
Order By: Relevance
“…In contrast to our hypothesis, several recent studies have proposed a protective role for BMK1 activation in cardiovascular injury (11,45). With regard to such a model, it seems undeniable that the activation of BMK1 in the cuff-injured artery was the result of a compensatory response to the injury.…”
Section: Discussioncontrasting
confidence: 49%
“…In contrast to our hypothesis, several recent studies have proposed a protective role for BMK1 activation in cardiovascular injury (11,45). With regard to such a model, it seems undeniable that the activation of BMK1 in the cuff-injured artery was the result of a compensatory response to the injury.…”
Section: Discussioncontrasting
confidence: 49%
“…In EC, laminar flow activates PPARγ activity and activation of PPARγ exerts anti-inflammatory effects since PPARγ ligands reduce TNF induced VCAM-1 expression [29]. We have shown previously that flow-induced PPARγ activation is dependent upon ERK5, and is functionally important because expression of dominant negative PPARγ decreased the ability of ERK5 to decrease VCAM-1 expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent knock-out studies revealed an indispensable role of the MEK5/Erk5 cascade in embryonic vascular development and maintenance of vascular integrity in mature blood vessels (2, 8 -10). Erk5 further was shown to mediate shear stress-dependent repression of inflammatory responses via interaction with PPAR␥1 (11) and regulates flow-mediated expression of KLF2 (12), a mechano-activated transcription factor that controls various vasoprotective, anti-thrombotic, and anti-inflammatory responses to laminar flow (12)(13)(14)(15). However, Erk5 is * This work was funded by Deutsche Forschungsgemeinschaft Grants GO 811/1-5 (to M. G.) and GRK880/3 (International Research Training Group Vascular Medicine, Graduiertenkolleg 880/3 (to M. S. and M. G.)).…”
mentioning
confidence: 99%